Two new species of deep water south Brazilian turriforms (Neogastropoda, Conoidea, Turridae and Cochlespiridae) - Simone, Luiz Ricardo Lopes de; Tarasconi, José Carlos (Papéis Avulsos de Zoologia, 2022)
Two deep water new species of turriforms are described from south Brazilian coast. One of them is the turrid Polystira tupan sp. nov., one of the largest species of the genus (~80 mm), with proper sculpture, shallow anal notch, collected off Santa Catarina, 350 m. The other is a cochlespirid that has been confused with Cochlespira elegans, a north Atlantic species; as it has different sculpture, shape, peripheric spines, etc., a new species, Cochlespira notomaris sp. nov., is introduced, occurring so far from off Santa Catarina to Rio Grande do Sul, 200‑1,000 m. For comparative purposes, the holotype of C. elegans is also illustrated.